Non-AUG Translation Initiation Generates Peroxisomal Isoforms of 6-Phosphogluconate Dehydrogenase in Fungi - Kremp, Marco; Bittner, Elena; Martorana, Domenica; Klingenberger, Alexander; Stehlik, Thorsten; Bölker, Michael; Freitag, Johannes (Frontiers in Cell and Developmental Biology, 2020)
Proteins destined for transport to specific organelles usually contain targeting information embedded in their sequence. Many enzymes are required in more than one cellular compartment and different molecular mechanisms are used to achieve dual localization. Here, we report a cryptic type 2 peroxisomal targeting signal (PTS2) encoded in the 5’ untranslated region (5’ UTR) of fungal genes coding for 6-phosphogluconate dehydrogenase (PGD), a key enzyme of the oxidative pentose phosphate pathway. Conservation of the cryptic PTS2 motif suggests a biological function. We observed that translation from a non-AUG start codon generates an N-terminally extended peroxisomal isoform of Ustilago maydis PGD. Non-canonical initiation occurred at the sequence AGG AUU consisting of two near-cognate start codons in tandem. Taken together, our data reveal non-AUG translation initiation as an additional mechanism to achieve dual localization of a protein required both in the cytosol and peroxisomes.